How Pharmacists Can Assist Physicians With Controlling Blood Pressure - Carter, Barry L. (J Clin Hypertens (Greenwich), 2007)
The goals for hypertension in the publication Healthy People 2010 require a much more intensive approach in order to achieve desired blood pressure control rates. The pharmacist is uniquely positioned in the health care system to assist with improving blood pressure control by utilizing strategies to solve medication‐related problems. Studies within integrated health systems have demonstrated that when pharmacists are included as members of health care teams, control rates for hypertension increase. In addition, drug interactions, nonadherence, and costs can be reduced. The authors suggest that incorporating a pharmacist or some services typically provided by traditional pharmacists into physician practices can improve blood pressure control. This review summarizes studies involving pharmacist participation in hypertension management and provides recommendations for obtaining pharmacist involvement.